Desenvolvimento de um Questionário de Experiências de (In) Validação Emocional na Família - Dinis, Alexandra (2011)
Several studies have confirmed the existence of a relationship between adverse early experiences, parenting styles and attachment in infancy with the development of psychopathology in adulthood. This study explores the psychometric properties of the Emotional (In) Validation Experiences Questionnaire, which was developed by us, in order to assess retrospectively, the emotional validation (and invalidation) environment in family. The Exploratory Factor Analysis revealed a structure of two factors, which was later confirmed by a Confirmatory Factor Analysis. The two factors were designated by emotional invalidating experiences and emotional validating experiences. All sub-scales have an accurate internal consistency. The convergent and divergent validity of the questionnaire was confirmed by correlations with other retrospective measures (that assessing parenting styles, parental emotional expressiveness and early adverse experiences), and with a measure that assesses psychopathology in adulthood.